Extrapulmonary tuberculosis: Mycobacterium tuberculosis strains and host risk factors in a large urban setting in Brazil. - Teresa Gomes; Solange Alves Vinhas; Bárbara Reis-Santos; Moisés Palaci; Renata Lyrio Peres; Paola P Aguiar; Fabiola Karla Correa Ribeiro; Hebert Silva Marques; Valdério do Valle Dettoni; John L Johnson; Lee W Riley; Ethel Leonor Maciel (PLoS ONE)
Background Factors related to the development of extrapulmonary forms of tuberculosis (EPTB) are still poorly understood, particularly in high-endemic countries like Brazil. The objective of the paper is to determine host and Mycobacterium tuberculosis (MTB) strain-related factors associated with the development of EPTB in Espírito Santo state, Brazil. Methods and findings We conducted a retrospective laboratory-based surveillance study of new tuberculosis (TB) cases diagnosed in Espírito Santo state, Brazil between 1998 and 2007. We genotyped 612 isolates of MTB from 606 TB patients using spoligotyping and IS6110-restriction fragment length polymorphism (RFLP) typing and compared sociodemographic and clinical characteristics of patients with pulmonary TB (PTB) and EPTB. Among 606 patients, 464 (77%) had PTB, 79 (13%) had EPTB, 51 (8%) had both, and 12 (2%) had miliary TB. The IS6110 RFLP analysis demonstrated that 250 (41%) isolates belonged to clustered RFLP patterns, 27 (11%) of which were from EPTB. We identified 73 clusters including 35 (48%) composed of 2 isolates each. By spoligotyping, 506 (83%) MTB isolates fell into known patterns and 106 (17%) fell into patterns with no family assignment; 297 (48%) isolates belonged to the Latin-American Mediterranean family. Higher school level (4-7 years OR: 0.16 95% CI 0.34-0.73 and > 8 years of education, OR 0.06 95% CI 0.009-0.50) white ethnicity (OR: 2.54 95% CI 1.03-6.25) and HIV infection (OR: 16.83 95% CI 5.23-54.18) were associated with EPTB. No specific strain lineage or percentage of clustering was associated with EPTB. Conclusions These results demonstrate that risk factors for EPTB are related more to host than to MTB strain lineage characteristics.